E Service Quality, Trust and Satisfaction on Consumer Loyalty at Hospital: Kualitas Layanan Elektronik, Kepercayaan dan Kepuasan Terhadap Loyalitas Konsumen Rumah Sakit - Indayani, Lilik; Sumartik; Hanum, Galuh Ratmana; Adinda, Taskia Putri; Viranti, Adelia Eva (Universitas Muhammadiyah Sidoarjo, 2022)
Rapid technological advances in the industrialization era make companies move faster in meeting needs. Government regulations that limit the distance and capacity of hospitals are the main factors for the emergence of e-service quality. Doctors have started to limit face-to-face contact with patients to avoid the risk of contracting Covid-19. This of course provides a business idea for hospital digital health service providers to apply it in the form of services. The quality of electronic services is also very important for the hospital health business to promote superior products and services to reach loyal consumers. The purpose of this study was to determine the mediating effect of customer satisfaction on customer loyalty with e service quality and trust variables, an integrated health business strategy from the direct effect of e service quality and trust on customer loyalty. Descriptive research design with quantitative methods, where the population is taken from consumers who use Siti Khodijah Hospital throughout Sidoarjo, researchers use random sampling technique in distributing questionnaires using accidental sampling, anyone encountered can be used as a sample, by taking 120 samples with indicators and statement items as much as 20 items. The software used is SEM PLS Wrap3.0. The resulting output is an increase in service quality to e service quality in the health business, consumer behavior and environmental conditions that determine consumers are satisfied and believe in health business products and services for individual consumers in line with the development of digital technology with a significance level of t count greater than t table and the VAF value is less than 80%, which means that customer satisfaction as an intervening variable is able to partially mediate.